Dynamic obstacle avoidance for robot - Koh, Gim Sheng (2014)
As the field of Robotics is generally young compared to many others, there are many fields in which engineers and researchers alike have not been able to fully explore. One of such topic in Robotics is obstacle avoidance. The project will not only focus on the implementation and testing of obstacle avoidance algorithms, it will also include the development of a cheaper and smaller sized robot for any future research.